2009
DOI: 10.1002/stem.44
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for Nucleostemin in Embryonic Stem Cell and Neural Stem Cell Viability

Abstract: Stem cells have the remarkable ability to self-renew and to generate multiple cell types. Nucleostemin is one of proteins that are enriched in many types of stem cells. Targeted deletion of nucleostemin in the mouse results in developmental arrest at the implantation stage, indicating that nucleostemin is crucial for early embryogenesis. However, the molecular basis of nucleostemin function in early mouse embryos remains largely unknown, and the role of nucleostemin in tissue stem cells has not been examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 49 publications
6
28
0
Order By: Relevance
“…However, in the current study, although caspase 3 was activated in response to NPR-C knockdown, the ES cells were maintained undifferentiated. In support to our results, a recent study has shown that loss of nucleostemin in ES cells leads to apoptosis with a dramatic increase in the levels of activated caspase 3 without affecting ES cell pluripotency [18]. Taken together, these findings suggest that loss of NPR-C may cause a low level of caspase 3 activation, which is not sufficient to induce differentiation.…”
Section: Npr-c Is Required For Es Cell Viabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…However, in the current study, although caspase 3 was activated in response to NPR-C knockdown, the ES cells were maintained undifferentiated. In support to our results, a recent study has shown that loss of nucleostemin in ES cells leads to apoptosis with a dramatic increase in the levels of activated caspase 3 without affecting ES cell pluripotency [18]. Taken together, these findings suggest that loss of NPR-C may cause a low level of caspase 3 activation, which is not sufficient to induce differentiation.…”
Section: Npr-c Is Required For Es Cell Viabilitysupporting
confidence: 88%
“…In ES cells, p53 is required to activate apoptosis [1,18]. We did not observe any increase in the levels of p53 mRNA ( Supplementary Fig.…”
Section: Npr-c Protects Es Cells From Apoptosis By Regulating P53mentioning
confidence: 44%
“…However, the precise effects of NS vary among different cell lines. For example, loss of NS in embryonic stem cells results in loss of cell viability over long-term culture, whereas the viability of NS null neural stem/progenitor cells can be sustained for more than 10 passages without losing neural stem cell marker expression and bipotency (Nomura et al 2009). Silencing NS in PC3 cells results in increased numbers of apoptotic cells (Liu et al 2008), whereas apoptosis was not enhanced in NSmutant mouse embryos (Beekman et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies about NS established the connection between NS and apoptosis populations (Nomura et al 2009). NS is concomitant with cellular proliferation and apoptosis, thus it is not surprising that NS-p53 pathway is activated in response to I/R and H/R.…”
Section: Discussionmentioning
confidence: 99%
“…NS possesses two putative GTP-binding motifs, and has been proposed as a marker for an undifferentiated or dedifferentiating state and for TICs in highly aggressive brain tumors (Kafienah et al, 2006;Tamase et al, 2009). The level of NS decreases drastically prior to cell cycle exit upon differentiation of the stem cells, suggesting that this protein may be an imperative protein for regulating the proliferation of stem cells and cancer cells, and in maintenance of their undifferentiated features (Jafarnejad et al, 2008;Nomura et al, 2009;Gao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%